2013
DOI: 10.1530/erc-13-0001
|View full text |Cite
|
Sign up to set email alerts
|

Ionizing radiation enhances dl922–947-mediated cell death of anaplastic thyroid carcinoma cells

Abstract: dl922-947 is an oncolytic adenovirus potentially suitable for the treatment of aggressive localized tumors, such as anaplastic thyroid carcinoma (ATC). In this study, we have analyzed the effects of dl922-947 in combination with ionizing radiations, testing different schedules of administration and observing synergistic effects only when ATC cells were irradiated 24 h prior to viral infection. Cells undergoing combined treatment exhibited a marked increase in cell death and viral replication, suggesting that i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
34
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(38 citation statements)
references
References 47 publications
4
34
0
Order By: Relevance
“…Previous studies have demonstrated that ionizing radiation, abnormal iodine intake, genetic factors and autoimmune disease are the primary factors contributing to the progression of ATC (4). Passaro et al (5) reported that ionizing radiation enhances the cell death of oncolytic adenovirus dl922-947 in ATC. Increased iodine intake contributes to a lower incidence of ATC (6), and it has been reported that forkhead box o3a enhances the proliferation of ATC cells via regulating the transcription factor, cyclin A1 (7).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated that ionizing radiation, abnormal iodine intake, genetic factors and autoimmune disease are the primary factors contributing to the progression of ATC (4). Passaro et al (5) reported that ionizing radiation enhances the cell death of oncolytic adenovirus dl922-947 in ATC. Increased iodine intake contributes to a lower incidence of ATC (6), and it has been reported that forkhead box o3a enhances the proliferation of ATC cells via regulating the transcription factor, cyclin A1 (7).…”
Section: Introductionmentioning
confidence: 99%
“…This may be exploited in the context of OVs that can stimulate cells to die by an alternative immunogenic fashion, thus rescuing ICD and establishing and antitumor immune responses. A recent study demonstrated that an adenovirus-based oncolytic (dl922-947) synergized with radiotherapy both in vitro and in an in vivo xenograft murine model of anaplastic thyroid carcinoma (Passaro et al 2013). Interestingly, this study demonstrated that enhanced killing of cancer cells was only seen when irradiation preceded viral infection.…”
Section: :12mentioning
confidence: 71%
“…Interestingly, this study demonstrated that enhanced killing of cancer cells was only seen when irradiation preceded viral infection. This was attributed to irradiation arresting cells in stages of the cell cycle that are more permissive to viral replication (G2/M) (Passaro et al 2013). Conversely, in another study, pretreatment with an adenovirus enhanced the susceptibility of several human cancer cell lines to irradiation.…”
Section: :12mentioning
confidence: 96%
“…Adeno 82,83 measles, 69 herpes simplex, 84,85 and vaccinia viruses 86,87 have been tested in vitro as well as in vivo in mouse explant models (Table 3). Conditionally replicative viruses include those that target cells with specific tumor suppressor pathways that have been [88][89][90] or are directed to negatively impact tumor growth such as targeting of angiogenesis.…”
Section: Preclinical and Clinical Studies Evaluating Potential Therapiesmentioning
confidence: 99%
“…Administration of an ATM (ataxia telangiectasia mutated) inhibitor KU55933 increases the oncolytic activity of the adenovirus dl922-947 in combination with ionizing radiations. 83 Oncolytic viruses (measles, vaccinia, and lentiviruses) expressing the NIS gene have been used to induce cell death as well as facilitate noninvasive imaging and radioiodine therapy. 69,86,94 Combinatorial therapeutic options using small molecule inhibitors such as paclitaxel, 84 bevacizumab, 89 gancliclovir, 95 and aurora kinase inhibitor AZD1152, 82 along with independent virus treatments, have also been evaluated preclinically.…”
Section: Preclinical and Clinical Studies Evaluating Potential Therapiesmentioning
confidence: 99%